UN FEMALE PEACEKEEPERS: AN ANALYSIS IN TERMS OF THEIR SERVICES - Farah Naz (Margalla Papers, 2021)
UN peacekeepers serve under harsh and dangerous conditions to help and support the most vulnerable people in conflict zones. The UN recognizes the importance of gender responses in peacekeeping engagements. It has expanded the role and contribution of women in peacekeeping and considers their role critical to enhancing overall peace and security. This paper, therefore, aims to study the cost-benefit analysis of the UN peacekeepers in terms of their services. The study is based on qualitative research using Pakistani female peacekeepers as a case study to draw analysis based on informal conversation/interviews with the former female peacekeepers, officers, and trainers. It also examines the current UN peacekeeping training module. This paper argues that the cost and benefits of the peacekeepers should be in line with the services required and concluded that focusing on peacekeeping operations is impractical without proper training and facilitation.